Influence of Body Mass Index on Heart Rate Variability (HRV) in evaluating cardiac function in adolescents of a selected Indian population (Italian Journal of Public Health, 2011)
Background: Heart Rate Variability (HRV) analysis is easy to perform, has good reproducibility and provides prognostic information about Coronary Heart Disease. Objective: This work was devised to correlate exercise induced HRV with BMI and compare gender variability among healthy Indian children aged 13-20 years. Methods: The Heart Rate Variability of sixty-five students in the 13-20 years age group was assessed by time- domain methods during resting and after exercise. On the basis of BMI, the subjects were grouped into T1 group (BMI
Keywords: Heart Rate Variability; Body Mass Index; nervous system; autonomic